Tong Hao—an Asian Vegetable Expanding in Florida - Guodong Liu; Qingren Wang; Bonnie Wells; Yuncong Li; David Dinkins (EDIS)
Tong Hao (Glebionis coronaria) is a member of the daisy family and therefore a relative of lettuce. It is an important vegetable in Asian communities. Grown in China for more than 900 years, Tong Hao is a branched annual leafy herb that can be cooked and eaten. This 6-page fact sheet provides background information about Tong Hao, including information on growing, harvesting, and cooking it. Written by Guodong Liu, Qingren Wang, Bonnie Wells, Yuncong Li, and David Dinkins, and published by the Horticultural Sciences Department, March 2016.